Use of nanoparticles to manage candida biofilms - Monteiro, Douglas Roberto (2020)
Candida species constitute an important part of the human oral microbiome and may be found as commensal colonizers in the oral cavity, as well as in the digestive and vaginal tracts. However, disturbances in host homeostasis may cause an overgrowth of these species, resulting in various types of candidiasis. This aspect, in conjunction with its ability to form organized and resistant structures, namely biofilms, has stimulated interest in nanotechnology-based therapies to fight biofilms and improve individuals’ health. This chapter approaches some of the clinical implications of Candida biofilms and their mechanisms of resistance to conventional antimicrobials, as well as the main types of nanoparticles used in controlling and preventing biofilms formed by different Candida species.